'Trump and Putin sittin' in a tree': material culture, slash and the pornographication of the 2016 US presidential election. Issue 4 (2nd October 2017) - Rowley, Alison
ABSTRACT: Drawing on examples from material culture and slash fiction, this article explores the pornographication of the 2016 US presidential election. Specifically, the article considers how the imagined 'bromance' between candidate Donald Trump and Russian President Vladimir Putin placed a same-sex relationship in the midst of the American political landscape, and brought increasingly hardcore pornographic references into the mainstream. The materials show that the existing alpha-male public persona of Putin was used as a foil for depictions of Donald Trump. The latter used pornographied imagery in order to satirize him as both a man and a political leader.